Biofunctionalized "Kiwifruit-Assembly" of Oxidoreductases in Mesoporous ZnO/Carbon Nanoparticles for Efficient Asymmetric Catalysis - Zhang, Rongzhen (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.